PROTECTIVE EFFECT OF FICUS CARICA FRUIT AGAINST CARBON TETRACHLORIDE INDUCED HEPATIC TOXICITY IN MICE - S. Hira 1; M. Gulfraz; S. M. Saqlan Naqvi; R. Qureshi; H. Gul; I. Shah (Journal of Animal and Plant Sciences, 2021)
Ficus carica (Fig) is considered to be first plant which is cultivated on earth. Fruit of this plant is delicious, medicinally important and is being consumed by human population since centuries. The present study was designed to assess the role of Ficus carica fruit as hepatoprotective agent in animal model. Crude methanolic extract of Ficus carica fruit and its derived n-hexane and aqueous fractions were used to study its curative effect on CCl4 induced toxicity in mice. Animals were divided into seven groups (n=5). Group I animals were treated with normal saline only, Group II was treated with olive oil (vehicle control), Group III was treated with CCl4 (toxic control) 0.2 ml/kg b.w, Group IV was treated with silymarin (standard drug) and Group V, VI and VII were treated with plant extract and fractions at different doses (200 mg/kg and 400 mg/kg b.w). Hepatoprotective effect was determined by investigating liver markers (Alanine transaminase, Aspartate aminotransferase, Alkaline phosphatase and bilirubin) using blood while in vivo antioxidant potential was found out by determining the activity of Glutathione peroxidase, Catalase and Superoxide dismutase. Histopathology of liver was also done. The aqueous fraction showed significant hepatoprotective effect against toxicity in mice as well as exhibited higher antioxidant value. The aqueous fraction of Ficus carica would be a good candidate for pharmaceutical industry as a hepatoprotective agent.
Keywords: Ficus carica; Hepatoprotective; Antioxidant; Carbon tetrachloride